Neuro- and Cardiotoxins from Sea Anemones: Structure, Function and Potential of Application in Research and Medical Practice - R. S. Kalina; M. M. Monastyrnaya (Вестник войск РХБ защиты, 2023)
Sea anemones are well-spread everywhere in the World Ocean and represent the most ancient active poisonous organisms. Their main instrument of attack on other animals are the nematocysts – stinging organelles with the curtailed hollow thread with poisonous edge on the end. In order to attract their potential victims, they use fluorescent proteins. These proteins became a separate object of research as genetically coded markers for the observation of activity of promotors of genes. The poisonous secret of sea anemones is characterized by the presence of maximum number of peptides of various structural classes and spatial structures among the studied land and marine organisms (bees, spiders, scorpions, snakes ect.). This fact complicates the identification of sea anemones' secret and its differentiation from poisons of animals of other taxons, if the concrete source of its origin is unknown. The toxicity of some biologically active sea anemone peptides (RpI, RpIII) at intravenous administration to experimental animals is comparable with that of the most well-known and dangerous representatives of natural toxins with the similar mechanism of action (an alpha-hemolysine and tetrodotoxin), or chemical warfare agents, such as sarin and hydrogen cyanide. Based on their toxic effect, the biologically active sea anemone peptides generally can be classified as neurotoxins due to their impact on the functioning of sodium channels in the cells of the nervous system of animals. Cardiotoxic effect of sea anemone secret is caused by the specificity of interaction between its separate neurotoxins and one of the sub-types of sodium channels of muscle cells, characteristic for heart tissues. The main ways of identification of sea anemone neurotoxins in samples (for example, during the investigation of biological crimes) can be sequence by Edman`s method or tandem mass spectrometry (the analysis of fragments of toxin molecule for the establishment of its structure). Further study on the mechanisms of interaction between the sea anemone neurotoxins and the ion channels of the cells of nervous and muscular systems may result in the creation of medicines for treatment of channelopathy, as well as pluripotential antidotes, blocking the toxins, that influence on sodium channels.